The Effect of Product Diversification on Purchase Intention Through Brand Trust, Perceived Value, and Customer Satisfaction in Premium Local Muslim Fashion Brands - Nia Puspita Hapsari; Suhendar Sulaeman; Liza Nora; Daman Sudarman (Green Publisher, 2026)
This study examines the effect of product diversification on purchase intention through brand trust, perceived value, and customer satisfaction in premium local Muslim fashion brands. The Muslim fashion industry is growing as part of lifestyle, creative economy, and digital marketing, yet brand success is not determined solely by market size. This research used a quantitative survey of 250 consumers who had purchased or were interested in purchasing Muslim fashion products. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed with Partial Least Squares Structural Equation Modeling using SmartPLS 4. The measurement model met convergent validity, discriminant validity, and reliability criteria. The structural model shows that product diversification significantly affects brand trust, perceived value, customer satisfaction, and purchase intention. Brand trust, perceived value, and customer satisfaction also significantly affect purchase intention, while brand trust strengthens perceived value. Mediation analysis confirms that perceived value, customer satisfaction, and brand trust partially mediate the relationship between product diversification and purchase intention, with customer satisfaction producing the strongest indirect effect.